Doação entre cônjuges no regime da separação obrigatória de bens da pessoa maior de 70 anos - Chaves, Yara Diwonko Brasil (2017)
This paper aims to demonstrate how the State actively interferes in the lives of its citizens, independent of the will and legitimacy of actions towards the protection of rights. The reduction of what is considered private gives rise to greater State incidence regulating what, at first glance, would be the exclusive choice of the human being as capable agent. Marriage is more than a union of souls, it is also a form of acquire goods. Although the state does not force anyone to get married, in some cases, requires the specific property regime. The implication of this forced choice, despite having justification in the protection of certain legal situations, eliminates the will and injures a right of personality, that is, freedom. The donation enters this merit to the extent that the citizen married in the scheme of compulsory separation of property is often hindered their right, because there is a very heterogeneous understanding of the donor's good faith in this type of asset transfer